Honduras : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report, 2005)
This report highlights progress made in implementing the Honduran Poverty Reduction Strategy (PRS) from the time of its approval by the Government of Honduras in August 2001 to the present. The report monitors the economic and social programs that were defined in the original document and which were revised following consultation with civil society in the First Progress Report and Update of the PRSP. The report discusses that Honduras has thus far achieved approximately 18 percent of the improvement on the PRSP indicators that will be needed to reach to the goals set for 2015.